Live and heat-killed cells of Lactobacillus plantarum Zhang-LL ease symptoms of chronic ulcerative colitis induced by dextran sulfate sodium in rats. (August 2020) - Jin, Junhua; Wu, Siqi; Xie, Yuanhong; Liu, Hui; Gao, Xiuzhi; Zhang, Hongxing
Graphical abstract: Highlights: Chronic UC rats Gavaged with live or heat-killed cells were of 100% survival rate. Live and heat-killed cells increased intestinal flora diversity of Chronic UC rats. Live and heat-killed cells reduced intestinal permeability of Chronic UC rats. Heat-killed cells were more effective against chronic UC in rats than live cells. Abstract: Controversial results were yielded in some studies on the effects of Lactobacillus on ulcerative colitis (UC). In this work, we evaluated the effect of live or heat-killed Lactobacillus plantarum Zhang-LL cells and cell supernatants on dextran sulfate sodium (DSS)-induced UC in rats. The tested subjects were gavaged to rats for 7 days, and then 5% was used DSS repeatedly to induce chronic UC. The results of a 42-day experiment, indicated consistently and significantly that Both living and heat-killed cells of L. plantarum Zhang-LL could down-regulate content of pro-inflammatory cytokines (TNF-α, INF-γ) in serum, reduce intestinal permeability by increasing the expression of tight junction proteins zo-1, claudin-1 and occludin in colon tissue, and maintain intestinal microbiota stability by increasing intestinal microbiota diversity to alleviate the symptoms of chronic UC in rats with 100% survival rate. Of concern is, the heat-killed cells of L. plantarum Zhang-LL were more effective against DSS-induced chronic UC in rats.